2019
DOI: 10.1186/s12913-019-4202-2
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive prescription among black patients without compelling indications: prescription, effectiveness, quality and cost of medication

Abstract: Background Hypertension remains one of the leading causes of death in Nigeria. Appropriate and cost-effective treatment of the disease is necessary to reduce mortality. This study evaluates (i) the prescription patterns and quality (ii) blood pressure control and (iii) cost of medication among patients with hypertension uncomplicated by co-morbid diseases or compelling indications. Method Patients with uncomplicated hypertension attending three clinics in the University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 30 publications
1
28
1
Order By: Relevance
“…Study characteristics are summarized in Table 1 , a more detailed version can be found in additional file 2 . Regarding the economic study design, 21 studies followed a partial economic evaluation (nine cost descriptions [ 33 , 35 – 38 , 44 , 47 , 49 , 56 ], eight cost analyses [ 41 , 45 , 46 , 48 , 50 , 57 , 58 , 64 ] and four cost-outcome descriptions [ 32 , 34 , 43 , 63 ]. The remaining studies followed a full economic evaluation design (seven cost effectiveness analyses [ 39 , 40 , 54 , 59 62 ], three cost utility analyses [ 42 , 51 , 52 ] and two cost minimization analysis [ 53 , 55 ]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study characteristics are summarized in Table 1 , a more detailed version can be found in additional file 2 . Regarding the economic study design, 21 studies followed a partial economic evaluation (nine cost descriptions [ 33 , 35 – 38 , 44 , 47 , 49 , 56 ], eight cost analyses [ 41 , 45 , 46 , 48 , 50 , 57 , 58 , 64 ] and four cost-outcome descriptions [ 32 , 34 , 43 , 63 ]. The remaining studies followed a full economic evaluation design (seven cost effectiveness analyses [ 39 , 40 , 54 , 59 62 ], three cost utility analyses [ 42 , 51 , 52 ] and two cost minimization analysis [ 53 , 55 ]).…”
Section: Resultsmentioning
confidence: 99%
“…We identified convenient sampling [ 33 – 35 , 38 , 45 , 48 , 53 , 56 , 63 ] as the most used sampling method followed by random sampling [ 32 , 36 , 49 , 50 , 55 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies suggested that non-adherence behaviour could be predicted based on its' association with sociodemographic variables such as gender, age, ethnicity, religious affiliation, marital status, household, education background, employment status, and income. [7][8][9][10] Other predictors included comorbidity, 7,9,10 polypharmacy, 11,12 health belief 13 and health literacy. 14 Knowledge associated with these predictors would facilitate formulation of various interventions to improve medication adherence.…”
Section: Medication Adherence Among Hypertensive Patientsmentioning
confidence: 99%
“…This review is relevant for several reasons. First, hypertension-related mortality and morbidity disproportionately affects the Black population [16,17,[26][27][28], who are at a higher risk of polypharmacy due to the higher prevalence of comorbidities associated with or caused by HTN [29]. Second, a critical appraisal of the current evidence on the clinical bene ts and harms for Black people with EH is required.…”
Section: Importance Of This Reviewmentioning
confidence: 99%